HUBUNGAN ANTARA PENGETAHUAN PEKERJA TENTANG K3 DAN PENGAWASAN K3 DENGAN PERILAKU TIDAK AMAN (UNSAFE ACTION) - Ro'i Chatul Uyun; Evi Widowati (Jurnal Kesehatan Masyarakat (Undip), 2022)
A work accident is an unwanted and unexpected event that can cause human and/or property casualties. According to Heinrich 80–85% of accidents that occur are caused by unsafe actions, while the remaining 15–20% occur due to unsafe conditions.many cases happened to workers as carpenters who were perating woodworking machines in the accident data of PT. Pijar Sukma. The purpose of this study is to find out whether there is a relationship between workers' knowledge about K3 and K3 supervision and unsafe action. The type of this research is quantitative research with analytical observational method and cross sectional design. The number of respondents is 90 workers, using Stratified random sampling technique. The research instrument used a questionnaire. Data analysis used an Fisher's test. The results showed that the percentage of respondents with high knowledge was 79 (87.8%), low knowledge was 11 (12.2%). respondents who rated the supervision as good as 75 (83.3%), the supervision as not as good as 15 (16.7%). respondents who behave safely are 72 (80%), and 18 (20%). that there is a significant relationship between knowledge about K3 (p=0.039) and K3 supervision (p=0.010) with unsafe acts. The conclusion is that there is a significant relationship between OSH knowledge and OSH supervision with unsafe acts.